Jump! Boys - Goverment Information Office; Jumpboys Films ([Taiwan : Jumpboys Films, 2005)
These little boys come from different families and have unique characters and temperaments. They don't play computer games or hang out at McDonalds. Instead, they go straigh to the gymnasium after school, which is the only thing they have in common. The training is painstaking, yet they never quit. This is not tradisional or critical documentary films, as it potrays its story in a humorous and cheerful manner. The coach has to act like both a tough father and loving mother to his students
DVD Format
Subtitles in English, Tradisional Chinese, French and Spanish
Keywords: Gymnastics for children; Gymnastics for children -- Coaching; Gymnastics -- Training; Sports for children